Effect of different dietary strategies on gas emissions and growth performance in post- weaned piglets - Montalvo, G.; Morales, J.; Pineiro, C.; Godbout, S.; Bigeriego, M. (Spanish Journal of Agricultural Research, 2013)
The objective of this study was to assess the effects of different dietary strategies in post-weaned piglets on gas emissions and animal performance. Eighty piglets were allotted in ten environmentally-controlled chambers. Piglets were fed with five different isoenergetic diets: control, low protein (LP), inclusion of sugar beet pulp (SBP), addition of benzoic acid (BA) and a combination of LP, SBP and BA (LP+SBP+BA). The gases analyzed were ammonia (NH3), methane (CH4), nitrous oxide (N2O) and carbon dioxide (CO2). For NH3, the most effective treatment was LP, with a reduction of 61%. The LP+SBP+BA reduced NH3 emission by 51%, the inclusion of SBP by 43% and the least effective technique was BA, which decreased by 9.5%, compared to control. The CH4 emission was reduced by 30% for LP, but was increased by 23% for SBP and 24.6% for LP+SBP+BA. Benzoic acid did not differ from control group. The N2O emission did not show statistically differences, and CO2 and carbon dioxide equivalent (CO2eq) emission increased with LP+SBP+BA (14 and 15% respectively), but were not affected by other diets. No effect of dietary treatment was observed on the growth performances compared with control group (p >0.05). We can conclude that the best technique to reduce NH3 emission was LP. Inclusion of SBP decreases NH3 emission, but can increase greenhouse gas emissions. It would be interesting to evaluate the effect of higher percentages of BA because the promising results. Combining techniques is not a good strategy to obtain an additive effect in gas emissions reduction.